Pasture dragging fails to reliably suppress the emergence of horn flies (Haematobia irritans) and face flies (Musca autumnalis) from dung pats in a Mid‐Atlantic North American climate. Issue 1 (23rd August 2022) - Smith, Jason D.; Steiman, Matthew W.
Abstract: The beef industry endures major economic losses from a complex of flies that feed on bovine blood and mucus. For cattle on pasture, the most important of these pests are horn flies ( Haematobia irritans [L.] [Diptera: Muscidae]) and face flies ( Musca autumnalis [Diptera: Muscidae] De Geer). Pasture dragging to spread manure pats has been promoted as a management tactic for these species because their larvae inhabit bovine manure pats, but the efficacy of this practice has not been empirically validated. Spreading pats might promote fly mortality through desiccation or overheating, but these processes are weather‐dependent and warrant testing in disparate climates. We evaluated pasture dragging effects while monitoring for weather interactions throughout nine experiment rounds in summers of 2018 and 2020 in Pennsylvania, USA. The manure spreading treatments increased pat surface area up to 300% but failed to significantly reduce emergence of horn flies and face flies as compared to controls. In contrast, precipitation and temperature were significant predictors in fly emergence models. Surprisingly, face fly emergence was significantly elevated in dragged pats twice in 2020. These data call for a reevaluation of pasture dragging as a management technique for horn flies and face flies across a range of climates. Abstract : Pasture dragging has been promoted as a management technique for horn flies and face flies despite known abilities of larvae to navigate manure environments, and without empirical evidence of efficacy. Our two‐year field study quantified natural fly emergence from dragged and control pats. The data fail to support the hypothesis that pasture dragging reliably suppresses horn flies and/or face flies. In two experiment rounds, manure spreading significantly elevated emergence of face flies. Contrary to expected outcomes, these findings highlight the need to reevaluate applications of this fly management tactic.